Producao e melhoramento do feijao-de-vagem (Phaseolus vulgaris L.) no Brasil - Leal, N.R. (International Center for Tropical Agriculture, 1987)
Snap bean production and commercialization in Brazil are briefly analyzed. Seed production is the responsibility of a group of institutions located in various states. Breaktrhoughs in genetic improvement by the Programa Nacional de Pesquisa de Hortalizas are described. (CIAT)